1959
DOI: 10.1136/sti.35.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Non-gonococcal Urethritis with Sigmamycin: A CONTROLLED METHOD OF INVESTIGATION

Abstract: Many different drugs have been tried for treating non-gonococcal urethritis (NGU) with varying degrees of success; this report describes an attempt to evaluate the effect of Sigmamycin at two different dosage levels.Sigmamycin is a 2 :1 combination of the antibiotics tetracycline hydrochloride and oleandomycin phosphate, and the claim has been made that this combination exhibits a synergistic action, so that the two drugs together are more potent than the sum of the individual components. To test this claim tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
1969
1969

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Discussion It has been shown that early "cure" of NGU after a placebo or with no treatment at all can be expected in 20-25 per cent. of cases (Doyle and others, 1957;Willcox, 1957;Leach, 1959;Csonka, 1959) and, as it is generally accepted that administration of the broad-spectrum antibiotics is followed by an early response in over 70 per cent. of patients (Harkness, 1953;Mayne, 1957;Willcox, 1957;Morton and Read, 1957), it was possible to dispense with untreated controls in this series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion It has been shown that early "cure" of NGU after a placebo or with no treatment at all can be expected in 20-25 per cent. of cases (Doyle and others, 1957;Willcox, 1957;Leach, 1959;Csonka, 1959) and, as it is generally accepted that administration of the broad-spectrum antibiotics is followed by an early response in over 70 per cent. of patients (Harkness, 1953;Mayne, 1957;Willcox, 1957;Morton and Read, 1957), it was possible to dispense with untreated controls in this series.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by several investigators that the tetracycline group comprise the most effective antibiotic therapy in non-gonococcal urethritis (NGU), although no drug or combination of drugs so far tried has been entirely successful in this condition (Harkness, 1953;Doyle, Gill, and Laird, 1957;Willcox, 1957;Leach, 1959;Csonka, 1959; and many others).…”
mentioning
confidence: 99%
“…The clinical effect of lincomycin in NGU one week after the start of treatment appeared to be no better than that of a placebo (Leach, 1959;Csonka, 1959); however, in a few patients improvement was prompt and in these lincomycin may have had an effect.…”
Section: Discussionmentioning
confidence: 99%